Cosmopolitan boundaries in Singapore : a study of Singaporean film - Lim, Shane Han Jung (2019)
While, in most cases, the discourse of cosmopolitanism is seen as a unifying step from divisive social structures, I argue in this thesis that the state’s vision of cosmopolitanism instead facilitates social inequality, through the state’s control of the urbanscape and the way space is produced. In order to do so, I examine four independent, Singaporean films, Mee Pok Man and 12 Storeys, by Eric Khoo, Eating Air, by Kelvin Tong and Jasmine Ng, and Gone Shopping, by Wee Li Lin, to see how inhabitants of the city-state are entrapped, if they have recourse to escape, and ultimately, how they emulate cosmopolitanism. I thus contend that this social inequality is one that highlights the impossibility of escape for its population.